Land Suitability Evaluation on Pepper Plant in Bireuen Regency, Aceh Province - yusra yusra yusra; Muliana Muliana; Khusrizal Khusrizal; Dewi Sartika Aryani (UNIVERSITY OF LAMPUNG, 2022)
Pepper plant development requires data and information on land potential and land suitability class assessment based on the physical and chemical properties criteria so that the land can be productive. The study aimed to determine the land suitability class for pepper plants in Bireuen Regency. The research was conducted in Bireuen Regency. The unit land map (Satuan Peta Lahan, SPL) resulting from the overlay of the slope map, land use map, and soil type map was used in this study. The method used is a survey method with a land unit approach consisting of four stages: (1) preparation stage, (2) preliminary survey, (3) main survey, and (4) presentation of results. The results showed that the land had good to poor drainage, soil depth >75 cm, flat to steep slopes, mild to very heavy erosion hazard, dusty clay texture, low to high cation exchange capacity (CEC), slightly acidic to slightly alkaline pH, low organic C, Base Saturation (BS) is low to high, N total is low to very low, P2O5 is very low, and K2O is very low. Land suitability class for pepper plants in Bireuen Regency includes marginal suitability (S3) with limiting factors in the form of drainage, texture, CEC, BS, N-total, P2O5, K2O, slope, and erosion hazard. Improvements include making rorak, planting contours, drainage systems, applying manure or compost, and planting cover crops.